THE IMPLEMENTATION OF MULTIPLE INTELLIGENCES IN TEACHING BASIC ENGLISH TO CHILDREN - Pipih Setiawati (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
In his multiple intelligence theory, Gardner (1993) sought to extend the capacity of human potential beyond the frame of the IQ score. Moreover, Gardner has grouped the capabilities into eight categories or intelligences. Those ntelligences are linguistic intelligences, logicalmathematical intelligences, spatial intelligences, bodily-kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence and the last one is naturalistic intelligence (Amstrong, 2002:2). According to Campbell’s experiences above, the writer is interested to investigate the Multiple Intelligences theory as teaching model especially in teaching basics English to children. All people posses all intelligences at varying levels, it is helpful for teachers to present content material through a variety of intelligences to make the information comprehensible to all learners.